Home IoT Authority Control Method Based on DID Auth - Choi, Jae Ho; Im, Jun Hyuk; Song, Hae Jun; Kim, Ki Hyung (International Conference on Ubiquitous and Future Networks, ICUFN, 2023)
The Home IoT device market is expanding rapidly, which has led to the increasing adoption of these devices in the home. However, IoT devices have long been challenged by various vulnerabilities and pose unique security challenges compared to other devices. This paper aims to redefine the process of entering the Home IoT environment by leveraging Decentralized Identifier(DID) authentication, and proposes a comprehensive approach to using Verifiable Credential(VC) and Verifiable Presentation(VP) to control access from outsiders like visitors. Through security analysis, this paper also highlights how these authentication and permission controls address traditional vulnerabilities and provide improved security over traditional IoT authentication methods. The results of this study shed light on the significant impact this methodology can have on the security of the Home IoT environment.
Keywords: Authority controls; Block-chain; Control access; Control methods; Decentralised; Decentralized identifier; Home IoT; Security; Security challenges; Verifiable credential·verifiable presentation; Authentication; Blockchain; DID; Home IoT; Security; VC·VP